Predictors of Clean Cookstoves Adoption by Households in Lagos State, Nigeria - S. A. Adebisi; F. O. Johnson (Unilag Journal of Humanities, 2019)
The adoption of Clean Cookstoves (CCS), which are clean, efficient, renewable andmodern forms of cookstoves and fuels, have shown mixed results globally. In SubSaharan Africa, the adoption rate of CCS is still at the lowest level despite persistentdeteriorating environmental conditions, rapid deforestation, climate change, healthhazards and rising mortality rate of women and young children as a result of the use oftraditional cookstoves and fuels. Several socio-economic, cultural, behavioural,institutional and environmental factors have been identified as critical factors influencingenergy cooking choice of households across the urban and rural regions. Drawing fromthe value chain framework and relevant literatures, fourteen (14) predictive factors wereidentified as critical factors for the adoption of CCS and fuels in Lagos State, Nigeria. Asurvey of 200 households on their perception of CCS adoption in Lagos Mainland LGA ofLagos State was carried out. The outcome of responses was analysed using the PartialLeast Square (PLS) Regression Technique. The results revealed that user’s preference,household’s affordability, CCS suitability, perceived benefits of using CCS, the transitionto CCS, level of education and accessibility of CCS are strong predictors of the adoptionof CCS by Lagos households; the remaining factors are low predictors. Additionally, theT-test results revealed that all the factors were significant at a 0.05, except for customsand belief which recorded a lower significant value. The study recommended that all theidentified fourteen (14) predictors should be considered as the value-added interactionsof factors are fundamental to the adoption of a new product or technology, however, thestrong predictors identified in the study should be given utmost consideration.